BATF3 promotes malignant phenotype of colorectal cancer through the S1PR1/p-STAT3/miR-155-3p/WDR82 axis - Li, Ping; Weng, Zhongpei; Li, Pengfei; Hu, Fangyong; Zhang, Yan; Guo, Zijian; Shen, Weibo; Zhao, Changyong; Dai, Saimin (Cancer gene therapy, 2021)
Encouraging insight into novel underlying mechanisms targeting abnormal biological pathways in colorectal cancer (CRC) are currently under investigation, edging closer and closer to clinical use. Of note, basic leucine zipper ATF-like transcription factor 3 (BATF3) has been implicated with the tumorigenicity of CRC. The current study aimed to elucidate the oncogenic BATF3-mediated S1PR1/p-STAT3/miR-155-3p/WDR82 axis in CRC. Initially, clinical samples of CRC tissues as well as CRC cell lines were collected to evaluate the expression patterns of BATF3/S1PR1/p-STAT3/miR-155-3p/WDR82. Dual luciferase assay was employed to assess the binding affinity between miR-155-3p and WDR82. Artificial modulation of BATF3 (down- and overexpression) was conducted to measure the malignant phenotypes of CRC cells, while tumor-bearing mice were examined to determine the in vivo effects. BATF3 facilitated the proliferative, migratory, and invasive potential of CRC cells by upregulating S1PR1. Besides, the stimulatory effect of S1PR1 was realized via restored p-STAT3 expression. Furthermore, p-STAT3 was evidenced to heighten the expression of miR-155-3p and subsequently restrict the expression of its target gene WDR82. The in vivo assays provided data further substantiating the in vitro findings that inactivation of the BATF3/S1PR1/p-STAT3/miR-155-3p/WDR82 axis suppresses CRC tumor growth. Collectively, the results of the present study emphasize the oncogenic function of BATF3 illustrated by the reinforcement the biological processes of proliferation, invasion, as well as the metastatic capacity of CRC cells through activating the S1PR1/p-STAT3/miR-155-3p/WDR82 axis.
"Published online: 14 October 2020".- S. 400
Gesehen am 23.09.2024